Analysis of surface quality of multi-film cooling holes in nickel-based single crystal superalloy. Issue 18 (11th December 2016) - Wen, Z.; Pei, H.; Zhang, C.; Wang, B.
Abstract : The effect of the surface quality of multi-film cooling holes processed by laser drilling (LD) and electrical discharge machining (EDM) on the mechanical properties of blades have been studied. The physical features of the cooling holes, including the diameter, conicity and shape of the holes, are measured by optical microscopy, demonstrating that the EDM process is not as accurate as the LD process. Meanwhile, metallurgical characteristics, including the recast layer, heat affected zone and micro-cracking within the surface layer, are analysed by scanning electron microscopy, demonstrating that the radial crack generated in the LD process is more dangerous than the circumferential cracks generated in the EDM process. Using finite element analysis (FEA), the single crystal superalloy specimens with multi-film holes are simulated based on the crystal plasticity theory, showing that a significant increase of the stress gradient is observed in a real hole model than in an ideal circular hole model, which means that a shape simplification in the blade design will reduce the reliability of the blade. Based on the findings above, the influence of the surface quality of holes is investigated to obtain the possible damages to nickel single crystal turbine blades.